It is more than sex and clothes: Culturally safe services for older lesbian, gay, bisexual, transgender and intersex people - Crameri, P.; Barrett, C.; Latham, Joe; Whyte, C. (Wiley-Blackwell Publishing Asia, 2015)
© 2015 ACOTA. This paper outlines the development of culturally safe services for older lesbian, gay, bisexual, transgender and intersex people. It draws on a framework for cultural safety, developed in New Zealand which incorporates an understanding of how history, culture and power imbalances influence the relationship between service providers and Maori people. This has been adapted to the needs of older lesbian, gay, bisexual, transgender and intersex Australians.